Bicruciate Ligament Reconstruction in a Professional Rugby Player: Clinical Presentation and Literature Review - Bohu, Yoann (Case Rep Orthop, 2015)
The association of an anterior cruciate ligament (ACL) tear and a posterior cruciate ligament (PCL) injury is rare in athletes, and to our knowledge it has never been described in a professional rugby player. We report the case of a 27-year-old international professional rugby player who presented with an ACL tear associated with chronic posterior laxity on a former PCL tear. The procedure associated arthroscopic ACL and PCL reconstruction in a one-stage operation with two autografts, bone-patellar tendon-bone and hamstring tendon, respectively. At 7 months postoperatively, the patient had returned to playing rugby at the same level of play. The therapeutic strategy successfully met the established goals of returning to sports at the same level of play with excellent functional results after 2 years of follow-up. A literature review was performed via PubMed. The inclusion criteria were the studies in English language, assessing the return-to-sport after bicruciate ligament reconstruction in athletes. Eight studies were included in analysis. Only one study has focused on the return-to-sport in 24 competitive athletes and two other studies have included 1 professional athlete each. The overall rate of the return-to-sport after bicruciate reconstruction varied between 100% and 50%.